THE ROLE OF ENTEROSORBENTS IN TREATMENT OF ENDOGENOUS INTOXICATION SYNDROME - N. I. Ursova ("Paediatrician" Publishers LLC, 2012)
Usage of enterosorbents in treatment of almost all types of acute and chronic disorders accompanied with endogenous intoxication syndrome takes on special significance. The critical point of endogenous intoxication pathogenesis is dysfunction of microbiocenosis and intestinal barrier. The necessity of enterosorbents usage is very high due to their efficacy, safety and wide availability. Smectite dioctaedric (diosmectite), which has been successfully used in clinical practice for a long period of time, is of an increased interest among the natural enterosorbents. The main quality of diosmectite is its restoration effect on the microbiocenisis and intestinal barrier function, and with a high degree of evidence-based efficacy and safety.